Influence of the process parameters on the energy conservation and quality of the kiwi fruit subjected to vacuum freeze-drying. (May 2022) - Wang, Bing-Bing; Sun, Pang-Yu; Chen, Bo-Lin; Sajjad, Uzair; Yan, Wei-Mon
Abstract: The aim of this is to investigate the energy conservation process and drying kinetics of the kiwi fruit subjected to vacuum freeze drying under different operating conditions. In this study, the influence of the three processes on product quality is studied, and the best process is highlighted in terms of appearance, color, taste, storage, nutritional ingredients, and cost. The differences of these processes are in the primary drying stage. For example, the sample temperature is lower than (process 1), equal to (process 2) or higher than (process 3) the eutectic point temperature. The results show that processes with sufficient primary drying time have lower final moisture content. During drying, the process 3 with a rapid temperature rise has better rehydration rate and microstructure. Overall, the best process is process 3, which has the highest performance index score, and its process time is short, which can save 35% of energy consumption compared to the other processes.